Association between body roundness index and frailty in older Americans: a cross-sectional study of NHANES 2007–2018 - Xu, Jie; Sun, Min; Chen, Meng; Lin, Zan; Hu, Yong; Luo, Xiaobing (Frontiers in Nutrition, 2025)
This study used NHANES data from 2007 to 2018 to examine the relationship between frailty and the Body Roundness Index (BRI) in U.S. people 60 years of age and older. BRI = 364.2–365.5 × sqrt [1–(wc/2π)2/(Height/2)2]. The degree of frailty was assessed by the frailty index (≥ 0.25). The relationship between frailty and BRI was examined using weighted multivariate logistic regression. To account for potential non-linear patterns, generalized additive modeling (GAM) was utilized, and the ability of BRI to predict frailty was assessed using receiver operating characteristic (ROC) analysis. Results showed that BRI was significantly and positively associated with prevalence of frailty, with a 34% increase in prevalence of frailty per unit increase in a fully adjusted model (OR: 1.34, 95% CI: 1.28, 1.40; p < 0.0001). The GAM model showed a significant nonlinear relationship and threshold effect. This study indicates that a higher BRI is closely linked to the onset of frailty in older adults, although additional confirmation through large-scale prospective studies is required.